Combined genome-wide association study of 136 quantitative ear morphology traits in multiple populations reveal 8 novel loci. - Yi Li; Ziyi Xiong; Manfei Zhang; Pirro G Hysi; Yu Qian; Kaustubh Adhikari; Jun Weng; Sijie Wu; Siyuan Du; Rolando Gonzalez-Jose; Lavinia Schuler-Faccini; Maria-Catira Bortolini; et al. (PLoS Genetics)
Human ear morphology, a complex anatomical structure represented by a multidimensional set of correlated and heritable phenotypes, has a poorly understood genetic architecture. In this study, we quantitatively assessed 136 ear morphology traits using deep learning analysis of digital face images in 14,921 individuals from five different cohorts in Europe, Asia, and Latin America. Through GWAS meta-analysis and C-GWASs, a recently introduced method to effectively combine GWASs of many traits, we identified 16 genetic loci involved in various ear phenotypes, eight of which have not been previously associated with human ear features. Our findings suggest that ear morphology shares genetic determinants with other surface ectoderm-derived traits such as facial variation, mono eyebrow, and male pattern baldness. Our results enhance the genetic understanding of human ear morphology and shed light on the shared genetic contributors of different surface ectoderm-derived phenotypes. Additionally, gene editing experiments in mice have demonstrated that knocking out the newly ear-associated gene (Intu) and a previously ear-associated gene (Tbx15) causes deviating mouse ear morphology.